Impact of Acid‐Reducing Agents on the Pharmacokinetics of Palbociclib, a Weak Base With pH‐Dependent Solubility, With Different Food Intake Conditions. Issue 6 (21st April 2017) - Sun, Wan; Klamerus, Karen J.; Yuhas, Lisa M.; Pawlak, Sylvester; Plotka, Anna; O'Gorman, Melissa; Kirkovsky, Leonid; Kosa, Maha; Wang, Diane
Abstract: Palbociclib free base capsule is a weak base drug with highly pH‐dependent solubility. In vitro and in vivo studies evaluated the impact of acid‐reducing agents on exposure of palbociclib and determined whether the impact, if any, can be mitigated by food. A drug‐drug interaction study (study 1) was conducted first under fasted conditions and showed that coadministration of multiple doses of the proton‐pump inhibitor rabeprazole substantially reduced palbociclib mean area under the concentration‐time curve from time 0 to infinity and maximum observed plasma concentration by 62% and 80%, respectively. In vitro assessment suggested that the presence of bile salt mixed micelles to mimic the fed state can significantly enhance the solubility of palbociclib. Subsequently, study 2 was conducted under fed conditions and demonstrated that coadministration of rabeprazole decreased palbociclib maximum observed plasma concentration by 41% but had limited impact on area under the concentration‐time curve from 0 to infinity (13% decrease). This study also showed that the histamine‐2 receptor antagonist famotidine and local antacid with staggered dosing had no impact on palbociclib exposure under fed conditions. Food intake effectively mitigated the impact of acid‐reducing agents on palbociclib exposure. Palbociclib free base capsule should be taken with food, and acid‐reducing agent use does not need to be avoided.